Strategic Pricing Models in Competitive Market - Sholikh Purnama Aji; Dina Dwi Febriyanti; Grace Amelia Indah; Lujeng Andini; Sabila Muyassaroh (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This article examines strategic pricing as a core function of marketing within a competitive market. The study aims to explore different pricing strategies such as penetration pricing, skimming pricing, value-based pricing, and competitive pricing. The methodology used includes qualitative content analysis based on current literature and case studies from Indonesian consumer markets. The findings suggest that successful pricing strategies are contextual and must align with customer value perception, competitor behavior, and overall brand positioning. The article concludes with practical recommendations for business practitioners in formulating pricing policies.